Declining trends in arthroscopic meniscus surgery and other arthroscopic knee procedures in Denmark: a nationwide register-based study - Matilde Lundberg; Jens Søndergaard; Bjarke Viberg; L Stefan Lohmander; Jonas B Thorlund (Acta Orthopaedica, 2022)
Background and purpose: A doubling of arthroscopic meniscal procedures was observed in Denmark from 2000 to 2011, but arthroscopic meniscal procedures for degenerative meniscal tears are no longer recommended. We performed an updated investigation of Danish meniscal procedure trends in the private and public healthcare sectors in Denmark from 2006 to 2018, including trends for other arthroscopic knee procedures. Patients and methods: We extracted data on the 5 most commonly registered arthroscopic knee procedures (diagnostic arthroscopy, meniscal surgery, anterior cruciate ligament reconstruction, synovectomy, and cartilage resection) from the Danish National Patient Register from January 1, 2006 to December 31, 2018, linked with the Danish Population Statistic Register, to obtain data on age and sex. Results: 414,253 arthroscopic knee procedures were registered during 315,290 surgeries on 244,113 individual patients in the study period. For meniscal procedures, the highest incidence was observed in 2010 (319 per 105 persons/year, 95% CI 314–323) and the lowest in 2018 (173 per 105 persons/year, CI 169–176), corresponding to relative decrease of 46% from 2010 to 2018. Remaining arthroscopic procedures also showed declining trends, with lowest incidence for all procedures in 2018. Interpretation: A large decrease in the incidence for arthroscopic meniscal procedures was observed from 2010 to 2018, possibly in response to mounting evidence of limited benefit of this procedure for degenerative knee disease. All other investigated arthroscopic knee procedures also declined in the same period.